Nationwide Eradication of Bovine Viral Diarrhea in Denmark: Strategies, Outcomes and Lessons (1994-2002) - Viggo Bitsch (Contemporary Research and Perspectives in Biological Science Vol. 10, 2025)
A fundamental feature of the epidemiology of the pestiviral Bovine Viral Diarrhea (BVD) infection is that a bovine fetus infected in its first trimester will not be able to identify the virus as a foreign agent because of which it will not produce antibodies when becoming immunocompetent. Surviving fetuses will, therefore, be delivered persistently infected, shedding the virus lifelong in all body secretions. Most importantly, the infection will be spread airborne following air movements. In 1991, it was evident that the eradication of BVD was desirable. The prevalence of the infection in cattle in Denmark was known to be very high. New sensitive Danish antigen and antibody ELISAs were available and a subunit BVD vaccine had been made at the State Veterinary Virus Research Institute, but their value had not been demonstrated. Methods to control and eradicate nationwide had never been tested anywhere. To clarify these questions, it was therefore arranged in collaboration with the Veterinary Virus Research Institute to perform the following three comprehensive pilot studies, 1) the vaccination efficacy study, 2) the test evaluation study, and 3) the Samsø island eradication study. The vaccine was found unable to prevent fetal infection in pregnant cattle, but the ELISAs appeared to be safe and well suited for an eradication program. A bulk tank milk reaction in the blocking antibody ELISA below 50 % of blocking would indicate BVD-free status (no presence of persistently infected animals), and a blood sample examination of just three young animals free from colostral antibodies could with acceptable reliability be used to indicate infection status and to confirm an earlier likely BVD-free status. Finally, the Samsø island eradication study demonstrated that eradication would be feasible. The pioneering decision to start eradication nationwide was taken by the farmers’ organizations with effect from January 1994. It was a huge advantage that the Danish Dairy Board had its own laboratory experienced in large scale control examinations and with any professional expertise. All test data were transferred to the central herd register also administered by the farmers’ organizations. After two years, the Danish Veterinary Service supported the program with legal provisions but still rejected mandatory eradication. The most important legal regulations were that animals to be moved to other herds, exhibitions, or common pastures had to be accompanied by a certificate issued after blood testing of the individual animals and that persistently infected animals were not allowed on pasture. In 1999, the trade certificate conditions were relaxed for herds having been free for over two years so that a blood test of animals to be moved no longer was required. From the course of the program, it could later be concluded that it would have been far more effective and less expensive, if legal provisions including mandatory eradication had been implemented right from the beginning. Nevertheless, a cost-benefit estimation later showed that expenses had been paid back within eight years. Veterinary practitioners had a central position. At regular intervals, they received circulars and overviews of the situation in dairy and non-dairy herds in their practice including deadlines for confirmatory free-status control for herds requiring control on blood samples. Introduction of persistent infection in earlier free herds was a severe problem over the whole period. For 67 dairy herds found infected in a one-year period from July 1997, (1) a few were infected because a pregnant heifer had become infected in a common pasture, (2) for 39% of the herds, persistently infected animals had been present at neighboring farms, and (3) for 25% of the herds no immediate possible cause could be found. It was concluded that airborne introduction had to be the cause, not only for a high proportion of the infected herds where persistently infected animals were present on neighboring farms, but also for most of the cases where no immediate cause could be observed. The most important experiences from the successful Danish BVD program are that the tests employed were supreme, that the lines selected for eradication and control were excellent, but also that eradication should have been mandatory right from the start. A such condition would most likely have reduced the eradication phase of the program to four years.